The fundamental right to education: an analysis of constitutional provisions in contrast to the factual reality (Research, Society and Development, 2020)
This study aims to analyze the dynamics of human rights, based on the Brazilian democratic platform established with the Federal Constitution of 1988, especially with regard to the fundamental right to education. With this, the limits of the democratic regime are pointed out as a field for the recognition and affirmation of human rights in Brazil, in concomitant application with the current constitutional legislation. In this perspective, this article, through descriptive research, of qualitative nature, deductive method, collection of bibliographic-documentary data, was carried out in order to perform a historical analysis of the right to education in the light of the Universal Declaration of Human Rights, as well as the Federal Constitution of 1988, mainly regarding the evolution of the right to education in Brazilian constitutionalism, in order to highlight the growth of the State's commitment to this right. Nevertheless, it also clarified the main incongruities regarding the quality of Brazilian education, which, despite the constitutional text will be arranged as a fundamental right that must be promoted by the State, is not effectively realized, being of relevant scientific interest the finding of the ins and outs that Brazilian education is conducted by the State. Moreover, it is noteworthy that, through the analysis of the sample indexes of the Brazilian educational quality, such as the IDEB, the verification of the real effectiveness of this right was asked. Finally, in view of the problem exposed, we sought, based on constitutional principles, to elucidate the need of the State, based on the defense of human rights and respect for social well-being, seeking the fostering of public policies as a way of social promotion.